Relatório do estágio curricular supervisionado em medicina veterinária área de concentração: produção avícola - (:unkn) unknown (Universidade Federal do Pampa, 2023)
The Supervised Curricular Internship in Veterinary Medicine took place in the city of Santa Helena - PR, at Lar Cooperativa Agroindustrial, in the Poultry Production concentration area, under the supervision of veterinarian Eliana Thais Riffel, at the Poultry Breeding Unit (URA). Breeders have a longer production period and are responsible for generating fertile eggs that will later culminate in the development of broiler chicks. These will be taken to the employees who are in charge of them until the moment they are sent to the slaughterhouse for slaughter. The stage began on August 7, 2023, and ended on October 30, 2023, thus totaling 520 hours. During this period, several breeding activities were carried out, as well as the preparation of sheds for housing the birds, monitoring of various feeding systems, vaccinations, selection management according to weight categories and other nucleus routines. The URA has a structure, containing 15 centers, the majority of which are made up of five sheds, four for females and one for males. To this end, this report aims to provide a description of the internship site, as well as the activities carried out and the discussion on biosecurity, which ensures the safety of the batches, prioritizing animal welfare.
Curricular internship report supervised in veterinary medicine area of concentration: poultry production
Keywords: Poultry farming; Poultry management; Poultry matrices; Production; Avicultura; Manejo avícola; Matrizes de aves; Produção; CNPQ::CIENCIAS AGRARIAS